OVER CAPACITY NARAPIDANA DI LEMBAGA PEMASYARAKATAN, FAKTOR PENYEBAB, IMPLIKASI NEGATIF, SERTA SOLUSI DALAM UPAYA OPTIMALISASI PEMBINAAN NARAPIDANA - Angkasa Angkasa (Jurnal Dinamika Hukum, 2010)
Overcapacity happened because growth rate dweller of ill assorted prison with dwelling medium of prison. Besides seems there are some other impeller factors to the happening of the paradigm overcapacity or law factors of itself which tend to oriented  institutional crime (prison). Overcapacity tend to to have negative implication to some matters for example the lowering of security storey;level / observation and also the happening of prisonization. Solution of overcapacity convict in prison in the effort optimalization construction of convict in the effort optimalization construction of convict for example with a few actions having the character of non-institutional in the form of conditional crime, probation, suspended, compensation, restitution and also usage of restorative justice. Keyword: overcapacity, convict, justice restorative